Evaluation of Reading Empowerment Asserting Connection at Home (REACH): Performance of Grade 7 Learners - Aira Nina Bautista Cosico (Journal of English as A Foreign Language Teaching and Research, 2024)
In the Philippines, reading is a persistent challenge that requires continuous remediation with the results of the Program for International Student Assessment (PISA) from both 2018 and 2022, and the country has been at the bottom of the rankings. Thus, the goal of this study is to strengthen reading remediation. This study focused on the evaluation of a reading program implemented; the Reading Empowerment: Asserting Connection at Home (REACH), and its relationship to the performance of Grade 7 learners in relation to reading. The participants of this study were 96 secondary school English teachers because they are field implementers of the reading program and were selected through a proportional stratified random sampling to ensure that each cluster was represented.  The study collected MPS results from three successive school years and evaluated the implementation of the reading program. The questionnaire was validated and researcher-made. Based on the findings, the hypotheses were partially supported. It was revealed that there was a significant relationship between the REACH evaluation and the school’s reading performance, particularly between the Product evaluation and the school’s reading performance during SY 2022-2023, and between the overall REACH evaluation and the school’s reading performance during SY 2023-2024. Furthermore, there was a positive relationship between the REACH Evaluation in terms of Context and Psychological Component. It was recommended that curriculum implementers continue the implementation of Reading Empowerment: Asserting Connection at Home (REACH), but this time, we focused on strengthening the other components of the CIPP Evaluation to improve the results of the reading program.